Місце маркетингових заходів у системі антикризового управління - Багорка, Марія Олександрівна; Bahorka, Mariia; Кадирус, Ірина Григорівна; Kadyrus, Iryna; Юрченко, Наталія Іванівна; Yurchenko, Nataliia (Національний авіаційний університет, 2021)
У статті проведено дослідження щодо визначення місця маркетингу в антикризовому управлінні підприємством, встановлена роль головних аспектів антикризового маркетингу на сучасних підприємствах; визначено складники маркетингового антикризового управління підприємствами з метою уникнення вразливості підприємства щодо кризових явищ та ліквідації їх наслідків. В авторському розумінні антикризове управління повинно охоплювати всі підсистеми управління підприємством: операційну, технічну, фінансову й особливо стратегічну, маркетингову, кадрову. Визнано, що в межах антикризового управління маркетинг виступає основним складником підсистем підприємства, а саме базою, яка забезпечує сталу роботу всіх його підрозділів. Виходячи з цього, в кризових умовах роботи підприємства або для превентивних заходів щодо запобігання використовуються традиційні інструменти маркетингу, але при цьому завдання маркетингових заходів набувають нових специфічних ознак, головною з яких виступає маркетингова антикризова програма. Враховуючи постійні зміни у середовищі свого функціонування, підприємства повинні розробити маркетингові програми, які передбачають заходи, що необхідно виконати для стабілізації ситуації на ринку і виходу з кризи неплатоспроможності. Логічним результатом такої програми є формування та імплементація маркетингової стратегії антикризового управління. The article conducts a study to determine the place of marketing in crisis management of the enterprise, established the role of the main aspects of crisis marketing in modern enterprises; mastered the mechanism of marketing anti-crisis management of enterprises, the purpose of which is to form a strategy for overcoming the crisis and eliminate the consequences of crisis phenomena. In the author's sense, crisis management should cover all subsystems of enterprise management: operational, technical, financial, and, especially, strategic, marketing, personnel. In the author's sense, crisis management should cover all subsystems of enterprise management: operational, technical, financial, and, especially, strategic, marketing, personnel. It is recognized that marketing in crisis management is not just one of the subsystems of the enterprise, but the basis that ensures the sustainability of all its other units. Anti-crisis marketing involves the prompt change of all components of marketing in accordance with changes in the environment, which helps to maintain maximum competitiveness of the company in market conditions. In the crisis of the organization or to prevent it, the same marketing tools are used as in stable conditions, but the goals and objectives of marketing activities change, which acquire new specific features, the main of which is the marketing anti-crisis program. The anti-crisis marketing program should ensure the production and sale of such goods that are in steady demand in the market and bring the company's main profit. The mechanism of anti-crisis marketing in the enterprise as a management system involves the presence of the object (crisis phenomena) and the subject of management, the formation of targeted management processes, subsystem monitoring environment and forecasting: determination of the stage, parameters, volumes and scales of the crisis phenomenon, development, implementation and control of anti-crisis strategies, etc.), choice of means and methods of management, creation of a clear system of adjustment and feedback. The end result of marketing anti-crisis management of the enterprise is the formation and implementation of marketing anti-crisis strategy.
Тhe place of marketing measures in the anti-crisis management system
Keywords: антикризове управління; anti-crisis management; антикризовий маркетинг; anti-crisis marketing; маркетингові заходи; marketing activities; антикризова програма; anti-crisis program; маркетингова стратегія; marketing strategy